Plastic Surgeons as Medical Directors: A Natural Transition into Medical Leadership - Jalalabadi, Faryan; Ferry, Andrew M.; Chang, Andrew; Reece, Edward M.; Izaddoost, Shayan A.; Hassid, Victor J.; Tahiri, Youssef; Buchanan, Edward P.; Winocour, Sebastian J. (Archives of Plastic Surgery, 2022)
With the growing complexity of the U.S. health care system, highly motivated medical directors with strong leadership skills are vital to the success of health care facilities. Presently, there are no articles assessing a plastic surgeon's qualifications for the role of medical director. In addition, there is a paucity of literature comparing the responsibilities of medical directors across various types of health care institutions. Herein, we outline why plastic surgeons have the unique skillset to succeed in this role and highlight the differences between medical director positions across the vast landscape of health care. While the intricacies of this position vary greatly across different landscapes of the health care industry, successful medical directors lead by following a set of universal principles predisposing them for success. Plastic surgeons innately exhibit a subset of particular traits deeming them suitable candidates for the medical director position. While transitioning from the role of a surgeon to that of a medical director does require some show of adaptation, plastic surgeons are ultimately highly likely to find intrinsic benefit from serving as a medical director.
Keywords: plastic surgery; physician executives; leadership; policy; academic medical centers